Ecoprise Entrepreneurial Model: Exploration of ecovillage design potential for a new entrepreneurial model - Velado, A.V.; Palumbo, S.; Mazaj, J.; Budrys, Z.; Esteves, A.M.; Gameiro, A.; Ferraro, D.; Vrenko, M.; Perry-Moore, A.; Solarevic, M.; Vujicic, V.; Gkrimoura, A.; et al. ((Tba), 2025)
This article introduces the Ecoprise entrepreneurial model, a framework designed to support regenerative social entrepreneurship by integrating ecovillage principles and permaculture ethics. Developed through empirical findings (based on the SWOT analysis) and theoretical insights, the model identifies seven core interconnected elements: Culture, Purpose, Regeneration, Ownership and Governance, Networks, Impact, and Repeatability. These elements create a flexible, collaborative framework emphasising ecosystem-based strategies over isolated entrepreneurship, focusing on environmental and social regeneration. The research reveals that successful implementation of regenerative strategies requires strong local collaboration, as current approaches face numerous challenges. Additionally, political, economic, and social factors significantly influence the scalability of social enterprises, especially in the context of the European Social Economy Action Plan, which aims to establish supportive environments across EU member states by 2025. The study also highlights skill and competency gaps essential for implementing regenerative practices, offering insights that address these challenges and guide the development of sustainable, resilient business models. Overall, the Ecoprise model contributes to existing literature by offering a practical framework for creating social and environmental impact and serves as a guideline and teaching tool for transitioning to regenerative business practices. By emphasising adaptability and ecosystemic collaboration, the model aims to support social entrepreneurs, educators, and policymakers in promoting a more inclusive and sustainable business landscape.